Effect of the quaternary ammonium compound trospium chloride on 24 hour jejunal motility in healthy subjects. Issue 1 (January 1994) - Schmidt, T; Widmer, R; Pfeiffer, A; Kaess, H
Abstract : This study aimed to record 24 hour jejunal motility in healthy ambulant subjects and to analyse changes in motility caused by the oral administration of an anticholinergic agent, the quaternary ammonium compound, trospium chloride. In a placebo-controlled, double blind crossover trial, 24 hour jejunal motility was recorded in 12 healthy volunteers, aged 25 (21-30) years, using a digital data logger connected to two strain-gauge transducers mounted 20 cm apart in a flexible nasojejunal catheter. A computer program was developed to determine contraction parameters. Trospium chloride (15 mg orally thrice daily) prolonged the duration of irregular contractile activity after meals (p < 0.02) and reduced its contraction frequency and amplitude (p < 0.001). In the fasting state, the cycle length of the migrating motor complex was prolonged (p < 0.01) by an extended phase I (p < 0.025). Phase III was shortened (p < 0.005) and showed a slower aboral migration velocity (p < 0.005). Clustered contractions were less frequent during postprandial and fasting periods (p < 0.01). Runs of clustered contractions were completely absent with trospium chloride. Digital manometry was useful for long term recordings of jejunal motility and enabled the motor effects of an anticholinergic agent to be characterised in ambulant subjects.